2015
DOI: 10.1155/2015/165430
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia and Associated Factors among Pregnant Women in North Western Zone of Tigray, Northern Ethiopia: A Cross-Sectional Study

Abstract: Background. Anemia affects the lives of more than 2 billion people globally, accounting for over 30% of the world's population. Anemia is a global public health problem occurring at all stages of the life cycle but the burden of the problem is higher in pregnant women particularly in developing countries. The aim of this study was to determine the prevalence of anemia and associated factors among pregnant women attending antenatal clinics in north western zone of Tigray, northern Ethiopia. Methods. A facility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
86
6
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(143 citation statements)
references
References 15 publications
39
86
6
12
Order By: Relevance
“…This prevalence was almost consistent with studies conducted in Awassa (15.1%), Gondar (16.6%), Debre Berhan (9.7%), Sudan (10%), Iran (13.6%), and Nakhon Sawan, Thailand (14.1%) [12, 16–20]. However, our finding is much lower than studies conducted in Pakistan (90.5%), India (87.2%), Malaysia (57.4%), Benin (68.3%), Nigeria (54.5%), Somali Region (56.8%), Walayita Sodo (40%), West Arsi zone (36.6%), and north western zone of Tigray (36.1%) [13, 2128]. Our result is also lower than results reported from Uganda (22.1%), Southern Ethiopia (29%), Southeast Ethiopia (27.9%) Mekelle (19.7%), and Addis Ababa (21.3%) [14, 2932].…”
Section: Discussioncontrasting
confidence: 77%
“…This prevalence was almost consistent with studies conducted in Awassa (15.1%), Gondar (16.6%), Debre Berhan (9.7%), Sudan (10%), Iran (13.6%), and Nakhon Sawan, Thailand (14.1%) [12, 16–20]. However, our finding is much lower than studies conducted in Pakistan (90.5%), India (87.2%), Malaysia (57.4%), Benin (68.3%), Nigeria (54.5%), Somali Region (56.8%), Walayita Sodo (40%), West Arsi zone (36.6%), and north western zone of Tigray (36.1%) [13, 2128]. Our result is also lower than results reported from Uganda (22.1%), Southern Ethiopia (29%), Southeast Ethiopia (27.9%) Mekelle (19.7%), and Addis Ababa (21.3%) [14, 2932].…”
Section: Discussioncontrasting
confidence: 77%
“…Like other studies, we did not find a relationship between anemia in pregnant Ethiopian women and dietary diversity, although dietary diversity has been shown to be associated with improved micronutrient adequacy [12,18,19,25]. However, dietary diversity was low for nearly all women in our sample.…”
Section: Discussionsupporting
confidence: 54%
“…schistosomiasis, hookworm infection), prior use of contraceptives, use of iron supplementation, birth spacing/intervals, parity and gravidity, educational attainment, age, body weight, trimester of pregnancy and wealth status. [6][7][8][9][10][11][12][13][14][15][16][17][18]. The relationship between anemia and dietary practices in Ethiopia has shown mixed results [12,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Residence, educational status, iron supplementation during pregnancy, and meal frequency per day were statistically associated with anaemia among the pregnant women. Awareness creation and nutrition education on the importance of taking iron supplementation and nutritional counselling on consumption of extra meal and iron-rich foods during pregnancy are recommended to prevent anaemia in the pregnant women 8 . Our study found that more than two third were anaemic that supports the finding that rural public deserved health education about importance problems of anaemia and malnutrition in pregnancy.…”
Section: Figure 1: Bmi Grades Of Participantsmentioning
confidence: 99%